2016
DOI: 10.1111/jgs.14304
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Insomnia in Older Veterans Using Nonclinician Sleep Coaches: Randomized Controlled Trial

Abstract: OBJECTIVES To test a new cognitive behavioral therapy for insomnia (CBT-I) program designed for use by nonclinicians. DESIGN Randomized controlled trial. SETTING Department of Veterans Affairs healthcare system. PARTICIPANTS Community-dwelling veterans aged 60 and older who met diagnostic criteria for insomnia of 3 months duration or longer (N = 159). INTERVENTION Nonclinician “sleep coaches” delivered a five-session manual-based CBT-I program including stimulus control, sleep restriction, sleep hygien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 43 publications
2
84
1
3
Order By: Relevance
“…Some participants, for example, reporting taking longer than 1 hour to fall asleep, but then reported that their sleep quality was "very good." Furthermore, in our recent insomnia treatment study of older veterans in the same health care system who were not participating in the ADHC program, 23 the mean baseline PSQI score was 9.1 and the mean baseline ISI score was 11.1, while their baseline sleep efficiency based on actigraphy was 83%. ADHC Patients in the current study had similar actigraphically assessed sleep efficiency (85%); however, their questionnaires reflected substantially less "complaint."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some participants, for example, reporting taking longer than 1 hour to fall asleep, but then reported that their sleep quality was "very good." Furthermore, in our recent insomnia treatment study of older veterans in the same health care system who were not participating in the ADHC program, 23 the mean baseline PSQI score was 9.1 and the mean baseline ISI score was 11.1, while their baseline sleep efficiency based on actigraphy was 83%. ADHC Patients in the current study had similar actigraphically assessed sleep efficiency (85%); however, their questionnaires reflected substantially less "complaint."…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this program was similar to CBT-I in terms of the number of sessions, but each session was shorter than many CBT-I intervention programs, which are typically 4-8 sessions lasting 60 minutes per session. 20,22,23 Some studies of brief interventions are also effective with older patients. 21,34 Consistent with traditional CBT-I interventions, all recommendations were tailored to the individual patient, addressing their specific circumstances, sleep patterns, and level of motivation to engage in the intervention.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disturbances in older adults are commonly addressed by sleep specialists. Given the shortage of clinicians specializing in assessing and treating sleep difficulties, it is imperative that sleep be evaluated routinely in other clinical settings and that alternative implementation models, such as using sleep coaches (Alessi et al 2016), be considered to reach more patients in need of effective treatments. Given the high prevalence of sleep disturbances, assessments need to be incorporated in regular health checks and referrals made for a thorough diagnostic workup when disturbances are reported, particularly given the evidence that it may represent a prodromal state of dementia.…”
Section: Future Opportunitiesmentioning
confidence: 99%